Hiatal hernia prevalence and natural history on non-contrast CT in the Multi-Ethnic Study of Atherosclerosis (MESA). Issue 1 (17th March 2021) - Kim, Jinhye; Hiura, Grant T; Oelsner, Elizabeth C; Yin, Xiaorui; Barr, R Graham; Smith, Benjamin M; Prince, Martin R
Abstract : Objective: To determine the prevalence, risk factors and natural history of hiatal hernia (HH) on CT in the general population. Materials and methods: The Multi-Ethnic Study of Atherosclerosis (MESA) acquired full-lung CT on 3200 subjects, aged 53–94 years. Three blinded observers independently determined presence/absence and type (I–IV) of HH. Associations between HH and participant characteristics were assessed via unadjusted and multivariable-adjusted relative risk regression. HH natural history was assessed compared with prior MESA CT. Results: Excellent interobserver agreement was found for presence (κ=0.86) and type of HH (κ=0.97). Among 316 HH identified (prevalence=9.9%), 223 (71%) were type I and 93 (29%) were type III. HH prevalence increased with age, from 2.4% in 6th decade to 16.6% in 9th decade (unadjusted prevalence ratio (PR)=1.1 (95% CI 1.04 to 1.1)). HH prevalence was greater in women (12.7%) than men (7.0%) (unadjusted PR=1.8 (95% CI 1.5 to 2.3)) and associated with proton pump inhibitor use (p<0.001). In 75 participants with HH with 10-year follow-up, median HH area increased from 9.9 cm 2 to 17.9 cm 2 (p=0.02) with a higher mean body mass index (BMI) in subjects with increasing HH size compared with HH decreasing in size: mean BMI=30.2±6.2 vs 26.8±7.2 (p=0.02). Conclusion: HH on non-contrast CT is prevalent in the general population, increasing with age, female gender and BMI. Its association with proton pump inhibitor use confirms a role in gastro-oesophageal reflux disease and HH progression is associated with increased BMI. Trial registration number: NCT00005487 .